The Process of Empowering the Artist in the Art Market - Kučinskaitė, Sima; Jurėnienė, Virginija (Vilnius University Proceedings, 2025)
The accessibility and purchase of artwork these days open up more opportunities for artists to exhibit, sell their work on a larger scale and gain recognition. However, simultaneously, there is high competition between all participants in the art market. Not knowing how to start, the creator faces challenges and obstacles to becoming a well-known art representative. In this case, artists can be helped by art galleries, which allow creators to show their creations and provide other support. In that instance, the gallery plays a role in empowering the artist to participate in the art market. Thus, this study aims to explore the process of empowering an artist to participate in the art market. It is important to understand how this process works and helps artists’ careers, so the presentation includes the results of research on artists and galleries, models, the empowerment process and emerging problems.